Electrostatic force-driven oxide heteroepitaxy for interface control - Ren, Zhaohui (2020)
Oxide heterostructure interfaces create a platform to induce intriguing electric and magnetic functionalities for possible future devices. A general approach to control growth and interface structure of oxide heterostructures will offer a great opportunity for understanding and manipulating the functionalities. Here, it is reported that an electrostatic force, originating from a polar ferroelectric surface, can be used to drive oxide heteroepitaxy, giving rise to an atomically sharp and coherent interface by using a low-temperature solution method. These heterostructures adopt a fascinating selective growth, and show a saturation thickness and the reconstructed interface with concentrated charges accumulation. The ferroelectric polarization screening, developing from a solid-liquid interface to the heterostructure interface, is decisive for the specific growth. At the interface, a charge transfer and accumulation take place for electrical compensation. The facile approach presented here can be extremely useful for controlling oxide heteroepitaxy and producing intriguing interface functionality via electrostatic engineering.